Architecture and Urban Studies in the complexity of the 21st century The FAU-UCE from the south - Echeverría Bucheli, Rosa Mishell (2021)
The architecture of cities currently faces a process of globalization with patterns that are changing urban, social, economic, and cultural structures towards the paradigm of complexity with dynamics in constant interaction, resulting for urban studies an intricate and difficult to understand set. This change requires a systemic vision to recognize both the properties of the object and the behavior of the subjects, around an architectural system, which together add up to more than the whole. Reflection from the academy is important, assuming an interdisciplinary teaching and with an epistemological vision from the global south.